Controlled vaporized cannabis, with and without alcohol: subjective effects and oral fluid‐blood cannabinoid relationships. Issue 7 (10th August 2015) - Hartman, Rebecca L.; Brown, Timothy L.; Milavetz, Gary; Spurgin, Andrew; Gorelick, David A.; Gaffney, Gary; Huestis, Marilyn A.
Abstract : Vaporized cannabis and concurrent cannabis and alcohol intake are commonplace. We evaluated the subjective effects of cannabis, with and without alcohol, relative to blood and oral fluid (OF, advantageous for cannabis exposure screening) cannabinoid concentrations and OF/blood and OF/plasma vaporized‐cannabinoid relationships. Healthy adult occasional‐to‐moderate cannabis smokers received a vaporized placebo or active cannabis (2.9% and 6.7% Δ 9 ‐tetrahydrocannabinol, THC) with or without oral low‐dose alcohol (~0.065g/210L peak breath alcohol concentration [BrAC]) in a within‐subjects design. Blood and OF were collected up to 8.3 h post‐dose and subjective effects measured at matched time points with visual‐analogue scales and 5‐point Likert scales. Linear mixed models evaluated subjective effects by THC concentration, BrAC, and interactions. Effects by time point were evaluated by dose‐wise analysis of variance (ANOVA). OF versus blood or plasma cannabinoid ratios and correlations were evaluated in paired‐positive specimens. Nineteen participants (13 men) completed the study. Blood THC concentration or BrAC significantly associated with subjective effects including 'high', while OF contamination prevented significant OF concentration associations <1.4 h post‐dose. Subjective effects persisted through 3.3–4.3 h, with alcohol potentiating the duration of the cannabis effects. Effect‐versus‐THC concentration and effect‐versus‐alcohol concentration hystereses were counterclockwise and clockwise, respectively. OF/blood and OF/plasma THC significantly correlated (all Spearman r≥0.71), but variability was high. Vaporized cannabis subjective effects were similar to those previously reported after smoking, with duration extended by concurrent alcohol. Cannabis intake was identified by OF testing, but OF concentration variability limited interpretation. Blood THC concentrations were more consistent across subjects and more accurate at predicting cannabis' subjective effects. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The subjective effects of vaporized cannabis are comprehensively characterized, with and without alcohol, and cannabinoid blood and oral fluid relationships evaluated. Oral fluid significantly correlated with blood, plasma, and subjective effects, with high intersubject variability. Vaporized cannabis produced similar subjective effects to smoked, but alcohol extended the duration of cannabis' effects.